(untitled) (Світ фінансів, 2017)
Марченко О. І., Погріщук Г. Б. Фінансове планування діяльності підприємств та напрями його розвитку. Висвітлено актуальні питання фінансового планування діяльності підприємств. Проведено моніторинг стану фінансового планування на промислових підприємствах Вінничини та окреслено напрями його подальшого удосконалення. Marchenko O., Pohrishchuk H. Financial planning of the activity of the enterprise and the directions of its development. The acute points of financial planning of enterprises’ activity are shown as well as the The acute points of financial planning of enterprises’ activity are shown as well as the results of monitoring of its state. The ways of further development are pointed out.